HaniAisya Hair Oil - Shu Mohd Fauzi, Shu Nur Aisyah Haninah; Bajiru, Norlaily; Husain, Nurul Amira (Multidisciplinary Applied Research and Innovation, 2022)
Coconut oil has many nutrients that can help to improve hair problems. The objective of this study is to produce hair oil made from coconut oil mixed with rice water and lemon essential oil which can treat hair problems. The second objective is to see the effect of using hair oil made from coconut oil mixed with rice water and lemon essential oil based on product quality aspects. This study uses a qualitative design. Qualitative data are obtained entirely from the structure interview method. The study sample consists of 20 respondents who have hair problems. The selection of the study sample focuses on the respondents who have damaged hair. Data will be analyzed to see the effects after using HaniAisya hair oil. Research results have shown that HaniAisya Oil could treat hair loss, coarse hair, oily and dried scalp, damaged hair, dandruff and scalp itchiness. Changes on hair could be seen as early as a week after application. Lemon fragrance can attract respondents’ interests in using HaniAisya hair oil onto their hair. Positive responses are given in regards to the texture of the produced oil. This innovation has convinced current generation faith on the healthiness of coconut oil that has been forgotten since ages ago. Henceforth, it will raise awareness among the society to use natural ingredients for hair rather than product that are harmful to consumers. It also contributes to the Industri Kecil dan Sederhana (IKS) where it can create employment opportunities for small entrepreneurs because it is produced from natural ingredients found in Malaysia.